Description of Maternal Parenting Patterns for Stunted Toddlers in Bello Sub-District, Maulafa District, Kupang City - Ledo, Juliatri; Litik, Serlie K. A.; Laga Nur, Marselinus; Berek, Noorce Ch (Timorese Journal of Public Health, 2025)
Stunting is a condition of impaired growth and development in children under five years of age due to chronic malnutrition and recurrent infections, especially during the first 1,000 days of life, from conception until the child is 23 months old. A child is classified as experiencing growth faltering when their height is below minus two standard deviations from the median height of children of the same age. This condition usually becomes apparent at around two years of age, and its impacts are irreversible. This research uses a descriptive study design with a survey method. The population includes all mothers in Bello Sub-District who have undernourished toddlers aged 2 to 5 years (more than 24 months up to 59 months). Samples were taken using an accidental sampling method. The findings indicate that maternal parenting patterns for undernourished toddlers are generally good. However, improvements are still needed in certain areas such as feeding practices ensuring balanced meal composition and avoiding coercive feeding and in environmental sanitation, particularly the condition of open wastewater drainage systems.